2016
DOI: 10.1016/j.jacc.2015.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Exercise at the Extremes

Abstract: Habitual physical activity and regular exercise training improve cardiovascular health and longevity. A physically active lifestyle is, therefore, a key aspect of primary and secondary prevention strategies. An appropriate volume and intensity are essential to maximally benefit from exercise interventions. This document summarizes available evidence on the relationship between the exercise volume and risk reductions in cardiovascular morbidity and mortality. Furthermore, the risks and benefits of moderate- ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
106
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 231 publications
(116 citation statements)
references
References 100 publications
5
106
0
5
Order By: Relevance
“…In patients with heart failure, serious adverse events were numerically higher with HIT than with MCT. This finding and the association of myocardial infarction, need for coronary intervention, and mortality in patients with CAD with exercise session duration or intensity, even though these findings are controversial, should receive attention in future trials 17, 18, 77, 119…”
Section: Exercise Prescriptionmentioning
confidence: 95%
See 1 more Smart Citation
“…In patients with heart failure, serious adverse events were numerically higher with HIT than with MCT. This finding and the association of myocardial infarction, need for coronary intervention, and mortality in patients with CAD with exercise session duration or intensity, even though these findings are controversial, should receive attention in future trials 17, 18, 77, 119…”
Section: Exercise Prescriptionmentioning
confidence: 95%
“…The authors concluded that running for even 5 to 10 min/d or 50 min/wk at a low speed of <6 miles/h (<10 km/h) markedly reduces the risk of death 13. However, in subgroups with the highest running intensity, the impact of running on mortality leveled off, whereas other trials even showed a loss of mortality reduction in healthy subjects and patients with CAD with high exercise intensities 10, 16, 17, 18. O′Keefe et al reviewed the pathophysiologic mechanisms of potential adverse cardiovascular effects from long‐term excessive endurance exercise, such as ultramarathons, ironman distance triathlons, or long‐distance bicycle races, which might diminish exercise‐related mortality benefits 19.…”
Section: Physical Inactivity As a Risk Factor For Cadmentioning
confidence: 99%
“…Prior studies have described the association between physical activity and CVD outcomes as curvilinear. 20,21 Although less reduction in CVD events was observed at high levels of moderate to vigorous activity, the protective effect for CVD mortality was still present as compared to those who were sedentary. 21 Another plausible explanation for why we might find a J-shaped association lies in the method of measurement of the outcome (CAC).…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Although less reduction in CVD events was observed at high levels of moderate to vigorous activity, the protective effect for CVD mortality was still present as compared to those who were sedentary. 21 Another plausible explanation for why we might find a J-shaped association lies in the method of measurement of the outcome (CAC). Although the Agatston method is the standard for scoring coronary calcification, some have suggested that other methods of determining coronary calcification should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is debate on the dose-response relationship of exercise and CVD outcomes [4,5] and whether high volumes of exercise may accelerate coronary atherosclerosis [6,7]. Nonetheless, CV prevention is in the first instance preferable by lifestyle changes, and many studies have shown an inverse association between physical activity level and the incidence of CVDs suggesting low aerobic fitness as a strong predictor for future CVD and all-cause mortality in both healthy and CVD patients [8,9].…”
mentioning
confidence: 99%